FREQUENCY AND COLLOCATION OF THE VERBS REFUSE AND REJECT - Diah Dwi Pratiwi (UC Journal: ELT, Linguistics and Literature Journal, 2020)
This research aims to study the occurrences frequencies and the collocations of the verbs refuse and reject. By looking at the collocations, it could be seen the context of the verbs occurrences. The objectives of this study are 1) to find out the frequencies of the verbs refuse and reject in Corpus of Contemporary American English (COCA) and 2) to find out the collocations of the verbs refuse and reject. The study was quantitative research and qualitative research. It used corpus study. The data were from COCA 2011 2012. The study used the purposive sampling method. The findings of this study showed that the frequency of the verb refuse was higher than the verb reject. The percentage of refuses frequency was 57.59%, while the percentage of rejects frequency was 42.41%. The collocations of the verbs refuse and reject were various. The collocations of the verb refuse were nouns, pronouns, and to infinitive forms. The collocations of the verb reject were nouns and pronouns. The verbs refuse and reject shared three similar collocations. They were money, treatment, him, and her, which represented a lover or someone who loved. Moreover, this study could support English learning and teaching. English Language Education Study Program students who were teacher candidates would aware of the use of synonymous verbs refuse and reject. They should clarify that those verbs could not been interchanged to another word.